A History of Women or Gender History? Opportunities, Limits, and Starting Points - Nečasová, Denisa (Dějiny – teorie – kritika, 2008)
The article provides a critical overview of research into the history of women and gender history of roughly the last three decades, focusing on the founding generation of American women historians. It considers in detail the debate that was called forth by the provocative, manifesto-like articles of Joan W. Scott, particularly ‘Gender: A Useful Category of Historical Analysis’. In addition, however, it discusses reserved approaches to historiography, which can be called feminist. With many small observations the article considers, for example, the limits of existing interpretations of approaches, the fuzziness of the definition of gender history, and the sometimes too narrowly defined conception of gender history as the history of power. The author briefly also considers Czech research, which hitherto has tended to concentrate on the history of women rather than gender history, and for the time being has not, with few exceptions, gone beyond the reception of English-language works and the methods they employ.